The Genealogy of Bram Stoker's Dracula: An Evolutionary Literary Analysis of The Vampire as a Meme - Aygun, Ahmet Anil (Technium Social Sciences Journal, 2020)
British author of Irish origin, Bram Stoker’s gothic horror novel, Dracula is the most reputed and popular example of the vampire literature that first emerged in seventeenth-century poetry. The first of the two key concepts that this thesis analyzes is the concept of “meme”, which was coined by the British evolutionary biologist Richard Dawkins, that can be defined as a thought, symbol or application transmitted from one individual to another via oral, written and visual methods and means of communication within a culture, replicates itself, transforms, responds to selective pressures, and the second concept is the memetic evolution of the vampire into the character, Dracula by Bram Stoker in Romantic ballads and Victorian horror narratives within the context of Evolutionary Literary Criticism which was theorized by Professor Joseph Carroll. In this regard, the qualities of the vampire phenotype that the Dracula meme inherited some qualities from its antecedent works of vampire fiction through memetic heredity, setting and plot are examined, and the evolutionary process that literary vampire predecessor had undergone towards the Transylvanian, aristocratic, seductive, stereotypical vampire. Finally, in the appendix, the prequels, sequels, and spin-offs of Dracula to demonstrate that the Dracula meme has survived and thrived notwithstanding over a century after its first publication and the selective pressures, and subsist by copying itself.